2015
DOI: 10.1007/s11701-015-0541-0
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study about haptic feedback in robotic surgery: may visual feedback substitute tactile feedback?

Abstract: The aim of this study is to demonstrate the hypothesis that the experience of the surgeon is sufficient to partially compensate for the lack of haptic feedback of the robotic system da Vinci Si HD (Intuitive (®) ). Twenty-five international surgeons belonging to different areas of surgical specialization were divided into two groups of investigation: experts and non-experts in the use of da Vinci Platform. This allocation was made on the basis of the following criteria: the number of performed procedures, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 12 publications
2
32
0
2
Order By: Relevance
“…TORS operations had a lower PMR than TLM procedures (17.4% vs. 20.0% for TLM), although open operations had the lowest (13.8%). The reduced tactile feedback of TORS may prevent head and neck surgeons from using their sense of touch to achieve negative margins and may explain the higher PMR in TORS relative to open operations of the larynx . The higher positive margin rate in TLM operations as compared to TORS is potentially due to the technical advantages of TORS over TLM.…”
Section: Discussionmentioning
confidence: 99%
“…TORS operations had a lower PMR than TLM procedures (17.4% vs. 20.0% for TLM), although open operations had the lowest (13.8%). The reduced tactile feedback of TORS may prevent head and neck surgeons from using their sense of touch to achieve negative margins and may explain the higher PMR in TORS relative to open operations of the larynx . The higher positive margin rate in TLM operations as compared to TORS is potentially due to the technical advantages of TORS over TLM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as [86] have demonstrated that expert surgeons could obtain significantly higher scores in experiments, than those of the non-experts. It is common to perform experimentation using participants with little/no surgical experience.…”
Section: Performance Metricsmentioning
confidence: 99%
“…This is because it has been demonstrated that the lack of this feature causes: (1) an increase in errors during the procedure (see e.g. [40,60,72]), (2) an increase in mental workload, which can complicate the task at hand and lead to irreversible damages (see e.g. [36,70]), (3) an increase in task-completion time (see e.g.…”
Section: Introductionmentioning
confidence: 99%